Anthropometry of the Medial Canthal Ligament Related to Naso-Orbitoethmoidal Fractures - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Objective: Medial canthal ligament (MCL) and lacrimal system are often associated with naso-orbitoethmoidal fractures. The MCL anchors tarsal plate to medial orbit and has an important role in lacrimal pump system. The purpose of this study was to describe the anatomy of the MCL and present the anthropometric measurements on cadaveric specimens. Methods: Dissections were performed on 14 formalin-fixed cadavers. The length, thickness, width of the MCL, width of the nasal dorsum, and intercanthal distance were measured with a digital caliper. A surgical microscope and an digital photo camera were used in all dissections. Means, SDs, and paired-samples t test were computed. Results: The mean lengths of the right and left MCLs were measured as 8.01 (SD, 2.27) and 7.93 (SD, 2.43) mm. The mean thicknesses of the right and left MCLs were 1.63 (SD, 2.41) and 1.75 (SD, 2.44) mm. The mean widths of the right and left MCLs were 4.20 (SD, 0.75) and 4.17 (SD, 0.61) mm. The intercanthal distance was 31.7 (SD, 1.7) mm. The width of the nasal dorsum was measured as 14.37 (SD, 1.9) mm. Length and thickness differed on both sides. Asymmetric insertion of medial canthi was observed in 5 specimens. Conclusions: Reconstruction of traumatic telecanthus requires reaproximation of medial canthi and the displaced nasoethmoid bony fragment with transnasal wiring or microplates. Identification and reconstruction of detached medial canthi could be accomplished sucesfully with anatomic familiarity of the region. The most developed and firmly adherent was the anterior limb of the MCL. Reattachment of that part seems to be adequate for repair of a detached canthus.
Keywords: Medial canthal ligament; naso-orbitoethmoidal fracture; anthrophometry; EYELID RECONSTRUCTION; HORNERS MUSCLE; ANATOMY; TENDON